2015
DOI: 10.1098/rspb.2015.0429
|View full text |Cite
|
Sign up to set email alerts
|

A test of genetic models for the evolutionary maintenance of same-sex sexual behaviour

Abstract: The evolutionary maintenance of same-sex sexual behaviour (SSB) has received increasing attention because it is perceived to be an evolutionary paradox. The genetic basis of SSB is almost wholly unknown in non-human animals, though this is key to understanding its persistence. Recent theoretical work has yielded broadly applicable predictions centred on two genetic models for SSB: overdominance and sexual antagonism. Using Drosophila melanogaster, we assayed natural genetic variation for male SSB and empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
(80 reference statements)
1
8
0
Order By: Relevance
“…Consistent with our findings, Hoskins et al [ 62 ] recently found an influence of sex-linked genetic variance in male SSB on female fecundity using four inbred lines from the Drosophila Genetic Reference Panel. However, the fact that male reproductive success was not scored made it difficult to assess the relative importance of overdominance versus SA selection in maintaining genetic variance in SSB [ 62 ]. Our data suggest that both shared and sex-limited SSB alleles have strong pleiotropic effects and that sex-limited selection on this behavioral trait can have SA fitness effects via cross-trait intersexual genetic correlations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our findings, Hoskins et al [ 62 ] recently found an influence of sex-linked genetic variance in male SSB on female fecundity using four inbred lines from the Drosophila Genetic Reference Panel. However, the fact that male reproductive success was not scored made it difficult to assess the relative importance of overdominance versus SA selection in maintaining genetic variance in SSB [ 62 ]. Our data suggest that both shared and sex-limited SSB alleles have strong pleiotropic effects and that sex-limited selection on this behavioral trait can have SA fitness effects via cross-trait intersexual genetic correlations.…”
Section: Discussionsupporting
confidence: 93%
“…Poor sex recognition can certainly affect rates of male-male mounting and studies in Drosophila provide an emerging understanding of the proximate basis for male SSB via this link (reviewed in: [ 27 , 28 ]). However, recent studies have only begun to uncover the underlying genetic basis of SSB in males [ 36 , 62 ] and the evolution of female SSB remains largely unexplored. Moreover, most previous studies have stopped short of exploring the link between standing genetic variation in SSB and fitness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SSB might also play important roles in mediating male competition (Lane, Haughan, Evans, Tregenza, & House 2016;Kuriwada 2017) and increasing relative fitness under sexual selection of males that express it (McRobert and Tompkins, 1988;Steiner, Steidle, & Ruther, 2005;Preston-Mafham, 2006;Bierbach, Jung, Hornung, Streit, & Plath, 2013). Despite these research efforts, little is known about the influence SSB might have upon evolutionary change of other traits (Bailey and Zuk, 2009;Scharf and Martin, 2013;Hoskins, Ritchie, & Bailey, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In captive animals, genetic, anatomical, neurophysiological, or hormonal investigations have failed to identify clear distinctions between the mechanisms that promote SSB versus HSB (Poiani 2010;Hoskins et al 2015). Even in humans, one of the most intensively studied vertebrate species, the abundant efforts to link sexual orientation with anatomy, physiology, and genetic mechanisms have revealed complex and equivocal patterns (Banks and Gartrell 1995;Rice et al 1999;Zitzmann and Nieschlag 2001;Mustanski et al 2002;Jannini et al 2010).…”
Section: Introductionmentioning
confidence: 99%